Forms of protection of the dentin-pulp complex: a literature review (Research, Society and Development, 2025)
Introduction: Dentin and pulp are co-dependent structures that together form the dentin–pulp complex. When this complex is subjected to aggression, such as deep carious lesions or trauma, it becomes necessary to protect these tissues. The aim of this study is to report the types of materials used and the advantages and disadvantages of each substance employed in the protection of the dentin–pulp complex. Methodology:This is a descriptive literature review (Snyder, 2019), qualitative in nature (Pereira et al., 2018), in a study with little systematization and of the narrative bibliographic review type (Rother, 2007). The search platforms used were the Virtual Health Library, Google Scholar, SciELO, and PubMed, and the terms used in the search for works were "dentin-pulp complex," "pulp capping," and "pulp-dentin and protection". Results and Discussion: The most prominent materials are glass ionomer, calcium hydroxide, and MTA due to their biological and mechanical properties. These materials are applied as protective agents for the dentin–pulp complex, liners, or bases for definitive restorations (Bausen et al., 2020). Final Considerations: Based on the information presented, it is evident that there is no material that possesses all the desired characteristics for the protection of the dentin–pulp complex. Therefore, it is important to emphasize that when selecting a material, the dentist should consider the advantages and disadvantages of each substance.